NEU1-Mediated Extracellular Vesicle Glycosylation in Alzheimer’s Disease: Mechanistic Insights into Intercellular Communication and Therapeutic Targeting - Mohd Adnan; Arif Jamal Siddiqui; Fevzi Bardakci; Malvi Surti; Riadh Badraoui; Mitesh Patel (Pharmaceuticals)
Alzheimer’s disease (AD), a progressive neurodegenerative disorder, is marked by the pathological accumulation of amyloid-β plaques and tau neurofibrillary tangles, both of which disrupt neuronal communication and function. Emerging evidence highlights the role of extracellular vesicles (EVs) as key mediators of intercellular communication, particularly in the propagation of pathological proteins in AD. Among the regulatory factors influencing EV composition and function, neuraminidase 1 (NEU1), a lysosomal sialidase responsible for desialylating glycoproteins has gained attention for its involvement in EV glycosylation. This review explores the role of NEU1 in modulating EV glycosylation, with particular emphasis on its influence on immune modulation and intracellular trafficking pathways and the subsequent impact on intercellular signaling and neurodegenerative progression. Altered NEU1 activity has been associated with abnormal glycan profiles on EVs, which may facilitate the enhanced spread of amyloid-β and tau proteins across neural networks. By regulating glycosylation, NEU1 influences EV stability, targeting and uptake by recipient cells, primarily through the desialylation of surface glycoproteins and glycolipids, which alters the EV charge, recognition and receptor-mediated interactions. Targeting NEU1 offers a promising therapeutic avenue to restore EV homeostasis and reduces pathological protein dissemination. However, challenges persist in developing selective NEU1 inhibitors and effective delivery methods to the brain. Furthermore, altered EV glycosylation patterns may serve as potential biomarkers for early AD diagnosis and monitoring. Overall, this review highlights the importance of NEU1 in AD pathogenesis and advocates for deeper investigation into its regulatory functions, with the aim of advancing therapeutic strategies and biomarker development for AD and related neurological disabilities.